Unique distribution pattern and δ13C signature of des-A-triterpenoids from Lake Wuliangsu: Source and paleoenvironmental implications. (December 2022) - He, Yuxin; Zhao, Qingfeng; Sun, Dayang
Highlights: des- A-triterpenoids from Lake Wuliangsu show a unique distribution pattern and source. des- A-triterpenoids can track submerged macrophytes in Lake Wuliangsu. des- A-triterpenoids are impacted by aerobic bacteria activities and photodegradation. Abstract: des- A-triterpenoids have been widely recognized as indicators of terrestrial vascular angiosperms and microbial activities. However, recent studies also suggested complex sources for des- A-triterpenoids in lakes and peatlands, thus complicating their applications in paleoenvironmental reconstructions. Here we present the occurrences of aliphatic and aromatic des- A-triterpenoids from a ∼160-year sedimentary core in Lake Wuliangsu in the upper reaches of the Yellow River, China. In these sediments, des-A-triterpane was not detected, whereas di-unsaturated des -A-triterpenes are more abundant than mono-unsaturated des -A-triterpenes. The δ 13 C values of di-unsaturated des -A-triterpenes range from –23.0‰ to –17.6‰, with an average value of –21.0‰. Accordingly, aliphatic des- A-triterpenoids from Lake Wuliangsu show a unique distribution pattern and more positive δ 13 C signatures compared with those sourced from terrestrial vascular angiosperms. By comparing the concentrations and δ 13 C values of des- A-triterpenoids with n -alkanes and triterpenoids, we suggest that des- A-triterpenoids from Lake Wuliangsu sediments might be degraded from oleanenone, which was produced by submerged macrophytes. In this sense, aliphatic des -A-triterpenes in Lake Wuliangsu could represent a novel proxy for submerged macrophytes, which would be more precise than those of mid-chain n -alkanes, considering that mid-chain n -alkanes are usually from multiple sources. Our results also demonstrate the importance of strong aerobic bacteria activities and photodegradation for the formation of di-unsaturated des -A-triterpenes. The aromatization process of aliphatic des -A-triterpenes show contrasting variation characteristic with the formation of aliphatic des -A-triterpenes over the past ∼160 years, probably due to different rates (production vs consumption of di-unsaturated des -A-triterpenes) and prerequisites (aerobic vs anaerobic conditions) for these two synthesis pathways.